The Influence of Slang on The Javanese Language Manners of Young People in Jombang - Aprilianti, Elok Dwi; Setyawan, Bagus Wahyu (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
Language is the identity of a country or a region, which is used as the main communication tool. Everyone needs language as a communication tool when interacting, language is also very useful for expressing ideas and opinions, as well as doing other social relationships. In the development of this increasingly advanced era, the use of the Javanese language is felt to have begun to shift and be replaced by the use of Indonesian, and the language of teenagers which is commonly referred to as slang. Slang users are in fact not limited to teenagers, it is not uncommon to find educated people who also use this slang, both in spoken and written form, both in formal and non-formal times, which results in the use of language being not good and not good. correct. Moreover, nowadays, along with the changing times with technology, it has also shifted some of the nation's culture, including the use of Javanese as the daily language of the Javanese people.